2021
DOI: 10.3390/met11020217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Thickness of the Reaction Zone in Aluminum/Stainless Steel Brazed Joints on the Mechanical Properties

Abstract: The study deals with the characterization of the relationship between the microstructure of the reaction zone and the mechanical properties in the brazed joints of aluminum alloy 3003 and stainless steel AISI 304 in order to determine the influence of the intermetallic layers on the tensile shear strength of the joints. The joints were produced by induction brazing using an AlSi10 filler in an argon atmosphere at a temperature of 600 °C. Due to the local heat input into the liquid brazing filler during a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Aluminum alloys are widely used in the automotive, aerospace, and electronics industries [1][2][3]. The task of reducing the weight of vehicles and aircraft through the use of lighter materials is caused by the desire to save fuel, economic benefits, and the environmental agenda [4]. In the automotive industry, aluminum alloys are used as radiator materials for heat dissipation devices, cylinder blocks, car body cladding, and so on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys are widely used in the automotive, aerospace, and electronics industries [1][2][3]. The task of reducing the weight of vehicles and aircraft through the use of lighter materials is caused by the desire to save fuel, economic benefits, and the environmental agenda [4]. In the automotive industry, aluminum alloys are used as radiator materials for heat dissipation devices, cylinder blocks, car body cladding, and so on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the formation of IMCs phases is highly dependent on thermal impacts, such as temperature and holding time, during the joining process. The IMCs layers at the interface adjacent to the steel are generally considered to be the main cause for the mechanical degradation of the joints [1][2][3][4][5][6][7][8][9][10] . It is of general interest to minimize the thickness of IMC phases at the joint interface by metallurgical methods and/or by the application of low interaction temperatures and short times to limit reaction and interdiffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there are a few reports on the brazing of Al alloys to steel/stainless steels by means of furnace brazing, vacuum brazing or even in air using flux for brazing. However, most of reported work were focused on the joining between Al alloys and stainless steel [1][2][3][6][7][8][9][10] , there is few reports on the brazing of pure Al to steels [4,5] which is one of the main joints of STJ.…”
Section: Introductionmentioning
confidence: 99%